All Aboard: Light Rail, Mobility Justice, and the Future of Public Transit in Austin, TX. - Karner, Alex; Shuster, Jonathan (Urban Affairs Review, 2025)
Activists and advocates are increasingly inserting themselves into urban governing regimes. Austin, TX offers a powerful example where these actors shifted public transit planning and decision making toward mobility justice—away from the demands of capital and toward everyday transit riders. Using primary source documents and 13 semistructured interviews with key participants, we demonstrate that a multibillion dollar voter-approved public transit expansion plan called Project Connect was undoubtedly shaped by activists and conceptions of mobility justice. Our results illuminate how these actors were able to influence the plan despite the marginalization of similar concerns in the American context. By engaging in the process early, shaping the initial investment plan that was put before voters, influencing project governance, and coalescing around a first-of-its-kind antidisplacement fund, activists created a permanent seat at the decision-making table from which they are able to fight for just processes and outcomes.